Alterations in Mucin-Associated Gene Expression on the Ocular Surface in Active and Stable Stages of Atopic and Vernal Keratoconjunctivitis - Mariko Horinaka; Jun Shoji; Akiko Tomioka; Yukiko Tonozuka; Noriko Inada; Satoru Yamagami (Journal of Ophthalmology)
Purpose. To evaluate the presence of ocular surface mucin in patients with atopic and vernal keratoconjunctivitis (AKC/VKC), we investigated the mRNA expression levels of SAM-pointed domain-containing ETS-like factor (SPDEF) and mucin-related genes on the ocular surface. Methods. Nineteen patients with AKC or VKC were divided into two groups based on the severity of the disease as determined by their clinical scores for AKC/VKC: the stable group and the active group. Impression cytology was performed in all patients using filter paper, and the expression levels of SPDEF, MUC1, MUC4, MUC5AC, MUC16, and eotaxin-2 mRNA were determined by real-time reverse-transcription polymerase chain reaction. Results. The results showed that the expression levels of SPDEF and MUC5AC mRNA in the active group were significantly decreased compared with those in the stable group. Furthermore, clinical scores were significantly negatively correlated with the expression levels of SPDEF mRNA and significantly positively correlated with the expression levels of eotaxin-2, which is a biomarker for eosinophilic inflammation on the ocular surface. Cluster analysis classified the patients with AKC/VKC into three clusters, and the stable group was divided into two clusters according to the condition of ocular surface mucin. Conclusions. Ocular surface mucin in patients with AKC/VKC is altered in accordance with the clinical severity of the disease.